Practical synthesis of indoles and benzofurans in water using a heterogeneous bimetallic catalyst - Cybille Rossy; Eric Fouquet; François-Xavier Felpin (Beilstein Journal of Organic Chemistry, 2013)
This paper describes the preparation of indoles, azaindoles and benzofurans in pure water by using a new heterogeneous Pd–Cu/C catalyst through a cascade Sonogashira alkynylation–cyclization sequence. Details of the optimization studies and the substrate scope are discussed. This procedure allows the preparation of heterocycles with good yields and is tolerant to a wide variety of functional groups.